A conceptual model for adaptation to climate variability in rangelands - Abedi, Mohsen; Hayati, Dariush; Valizadeh, Naser (Frontiers in Sustainable Food Systems, 2022)
Exploiting medicinal plants on rangelands is a climate-sensitive strategy in Iran. In other words, there is an urgent need for the transition toward resilience under current climatic pressures and risks. In addition, a deep understanding about awareness, risk perceptions, and adaptation strategies of different rural groups can play a significant role in the mitigation of climate change impacts and the development of the adaptation capacity. Therefore, the development of a conceptual model for adaptation to climate variability in rangelands was determined as the main purpose of the present study. To this end, we used analysis of awareness, risk perceptions, and adaptation strategies of medicinal plant exploiters toward climate variability. This research was carried out in Sought Khorasan province of Iran, which is one of the climate-sensitive and leading areas for the exploitation of medicinal plants in the country. Required data for this study were gathered through 13 focus group discussions. The number of members of these focus groups was between 4 and 12 people. The total number of participants in the focus groups was 91 medicinal plant exploiters. The results revealed that exploiters have a relatively favorable awareness of the current climate situation. However, they perceived huge constraints in financial supports and resources which lead to increasing social conflicts, decreasing social relations, leaving the job, increasing migration, unemployment, and psychological impacts. As expected, various adaptation strategies were used aiming at conserving, developing, improving, and managing income resources, but many of them are short of resilience orientation. Finally, research findings were articulated in the form of a conceptual model and some practical recommendations were presented to enhance adaptation of rangelands' exploiters.